Effect of cognitive styles, contexualised and decontextualised vocabulary teaching techniques and learning strategies on EFL vocabulary - Kıvanç, Ayşe Zeynep (My University, 2003)
The present study explores the effect of the cognitive construct of Field Dependence and Independence on vocabulary learning in an L2/ FL context together with two distinct vocabulary teaching techniques, namely word list as a decontextualised, and semantic mapping as a contextualised technique. To further investigate the reasons behind the outcomes of this research, the study also aimed to identify the subjects' habits, approaches and strategies toward vocabulary learning in English as a foreign language, their perceptual learning style preferences, and the relationship between native language proficiency and success in vocabulary learning. Forty A (upper-intermediate) level students at Yıldız Technical University, School of Foreign Languages, Basic English Department constituted the participants of the study. Cognitive style was measured by the Group Embedded Figures Test (GEFT) while their level of success in vocabulary learning was assessed by two English cloze tests, labeled Pre-test and Post-test. In order to measure the subjects' native language proficiency, two Turkish cloze tests were administered. Perceptual learning style preferences were ascertained by the Perceptual Learning Style Preference Questionnaire designed by Richards & Lockhart (1994). The data related to the approaches and strategies that the subjects adopted for vocabulary learning were elicited by means of the Vocabulary Learning and Study Strategies Questionnaire. The two Follow-up Questionnaires explored the extent to which the subjects adhered to the instructions given for two different vocabulary teaching techniques, namely word list and semantic mapping. Further to the manual and computerized computations, the data collected were processed by means of the Statistical Package for the Social Sciences (SPSS, version 10.0), which uses descriptive statistics, T-tests and Mann Whitney U-Tests. The findings of the study revealed that the subjects who were instructed to study vocabulary through the word list technique out-performed the subjects who studied vocabulary following the semantic mapping technique, which was in clear contrast to the findings reported in previous research. However, the analysis of the relationship between Field Dependency and Independency cognitive construct and the subjects' achievement level in vocabulary learning demonstrated that field independent subjects benefited from semantic mapping more than field dependent counterparts. It was also concluded from the results of this study that native language proficiency was a positive attribute for achieving a higher level of success in vocabulary learning as was the field independence cognitive style. The perceptual learning style preferences of the subjects did not contribute to the achievement level in vocabulary learning, presumably due to the small number of participants in the study. The data elicited by the two Follow-up Questionnaires and the Vocabulary Learning and Study Strategies Questionnaire revealed strong indications of a lack of awareness of the importance of learning vocabulary and that some of the subjects were not equipped with the appropriate attitude and effective study approaches to apply the semantic mapping technique in learning foreign language vocabulary. It was considered that their previously developed study habits throughout their educational life inspired a system of rote learning, which is likely to have hindered the cognitive inclination to make thematic associations among the vocabulary items causing a possible slow-down in learning vocabulary. In the light of these findings, limitations of the study were mentioned and some suggestions were made for further research. KISA

Bilişsel yordamların, bağlamlı ve bağlamsız sözcük öğretim tekniklerinin ve öğrenme stratejilerinin yabancı dil olarak İngilizce sözcük öğrenimine etkileri Bu çalışmada, bağlamlı ve bağlamsız olarak nitelendirilen ve birbirine zıt olan iki sözcük öğretme tekniği olarak anlam alanları şeması ile sözcük listesi uygulanmasında, bilişsel yordamlar (alana bağımlılık/ alandan bağımsızlık) ile sözcük öğrenimi arasındaki ilişki incelenmektedir. Ayrıca elde edilen bulguların sebeplerini araştırabilmek için, çalışmaya katılan öğrencilerin İngilizce sözcük öğrenme alışkanlık ve stratejileri, algısal öğrenme tercihleri ve anadildeki yeterlilikleri ile sözcük öğrenimleri arasındaki ilişkiye de bakılmıştır. Yıldız Teknik Üniversitesi, Yabancı Diller Yüksek Okulu, Temel İngilizce Bölümü'nde ileri-orta düzeyde İngilizce öğrenmekte olan 40 öğrenci bu araştırmanın denek grubunu oluşturmuştur. Öğrencilerin bilişsel yordamları Saklı Şekiller Grup Testi (GEFT) ile, sözcük öğrenme başarıları ise Ön-test ve Son-test olarak adlandırılan iki İngilizce 'çıkarmalı test' (cloze test) ile ölçülmüştür. Deneklerin ana dildeki yeterliklerini ölçmek için ise yine iki Türkçe 'çıkarmalı test' uygulanmıştır. Algısal öğrenme tercihlerinin belirlenmesinde Richards & Lockhart (1994) tarafından geliştirilen sormaca kullanılmıştır. Öğrencilerin sözcük öğrenme alışkanlık ve stratejilerine ilişkin bilgi, Sözcük Öğrenme ve Çalışma Stratejileri anketi ile, birbirine zıt iki sözcük öğretme tekniği uygulamasında nasıl bir çalışma yöntemi izlediklerine ilişkin bilgi ise uygulama sonrası verilen iki farklı anket ile toplanmıştır. Veriler, yapılan hesaplamalardan sonra, SPSS (10.0), T-testleri ve Mann Whitney U-testleri kullanılarak değerlendirilmiştir. Araştırmanın sonuçları sözcük listesi tekniği ile sözcük öğreniminin, anlam alanları şeması tekniği ile sözcük öğreniminden daha başarılı olduğunu göstermiştir; ki bu sonuç daha önce bu alanda yapılmış araştırmaların sonuçları ile açık bir zıtlık oluşturmaktadır. Sözcük Öğrenme ve Çalışma Stratejileri anketi ile uygulama sonrası anketlerinin bulguları, öğrencilerin sözcük öğreniminin öneminin farkında olmadıklarını, ayrıca bir kısım öğrencinin anlam alanları şeması tekniğinin gerektirdiği çalışma yöntemini uygulayamadıklarını ortaya koymuştur. Bu durumda, öğrencilerin önceki eğitim yıllarında geliştirdikleri çalışma alışkanlıklarının, büyük olasılıkla sözcükler arasında tematik ilişkilendirme yapma şeklindeki bilişsel yönlenmeyi engelleyen, böylelikle de sözcük öğreniminde olası bir yavaşlamaya neden olan ezbere dayalı öğrenimden kaynaklandığı yorumu getirilmiştir. Elde edilen diğer bir sonuç ise, ana dildeki yeterlik düzeyinin, yabancı dilde sözcük öğrenimine olumlu yönde katkısı olduğudur. Algısal öğrenme şekli tercihleri ile sözcük öğrenme başarısı arasında ise anlamlı bir ilişki gözlenmemiştir. Ancak, bilişsel yordam ile sözcük öğrenme başarısı arasındaki ilişki incelendiğinde alandan bağımsız olan öğrencilerin anlam alanları şeması tekniğinden daha fazla yarar sağladıkları saptanmıştır. Ayrıca sıralanan bulgular ışığında araştırmadaki sınırlayıcı faktörler belirtilmiş ve daha sonraki araştırmalar için bazı öneriler de sunulmuştur.
Keywords: İngiliz Dili